The Oxford handbook of Internet studies - Dutton, William H., 1947- (Oxford : Oxford University Press, 2013)
This handbook is a landmark in the dynamic and rapidly expanding field of Internet studies, bringing together leading international scholars to strengthen research on how the Internet has been studied and the discipline's fundamental questions, and shape research, policy, and practice for the future.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Internet -- Social aspects; Internet -- Economic aspects; Internet -- Law and legislation; Internet -- Study and teaching